Polityka oświatowa w Anglii w zakresie edukacji biotechnologii na tle przemian społeczno-kulturowych = Education policy in England concerning biotechnology education in the context of socio-cultural changes - Bryś, Katarzyna; Machnicka, Beata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This publication aims to show the impact of knowledge and understanding of biotechnological processes on all aspects of everyday life. Challenges of modern discoveries in biotechnology have forced the educational system in England to implement evaluation changes. The goal of education is the acquisition of scientific and technological knowledge required for the informed fulfilment of social responsibilities by the younger generation.
Keywords: edukacja biotechnologiczna; panel obywatelski; Anglia; England; biotechnology education; citizens` assembly